Pengaruh Penggunaan Media Sosial Terhadap Akhlak Siswa Madrasah Ibtidayah - Salsa Bila Khotrun Nada; Nina Novita; Naila Hafizah; Wismanto Wismanto; Najiha Azzahra (Jurnal Budi Pekerti Agama Islam, 2024)
This article examines the impact of social media on the morale of Madrasah Ibtidayah students. This is very interesting because many children abuse social networks. The purpose of this writing is to analyze the use of social media which influences students' moral education. Based on the interim analysis, we can see the positive and negative impacts of using social media on students' moral growth. The positive impact of the development of social media in children's moral education includes children's ability to adapt, communicate with society and manage friendship networks, as well as making tasks easier for children. The negative impacts of its development include neglect of children, so that children lack discipline and are lazy, so that children easily imitate other people's work, are rude both in dressing and speaking, often fight about dangerous things, scenes such as pornography, violence, war scenes. This research method uses a qualitative method with a library research approach which uses reading sources from books, magazines and journal articles related to the theme as the main source. The results of this research show that the use of social media has two effects, a good influence for those who are wise in using social media with adult guidance and a bad influence for those without guidance.